Multimodalidade e livro-brinquedo: entre práticas de leitura, brincadeiras e construção de sentidos - Aragão, Keila Gabryelle Leal (2023)
When we think that the texts are diverse and that they present a semiotic, representational and communicational variety, it is possible to infer that different modes, resources and materialities constitute it, understanding it as a “multimodal text” and that the adult has an essential role in reinforcing the perception of these elements with the child contributing to their development from a playful multimodal reading. In this scenario, the toy-book breaks with the conventional way of reading, breaking the boundaries commonly attributed to traditional books, to assume itself as a playful object of reading, in this way, the construction of the meaning of the text permeates an entire materiality that, together with other resources, promote countless experiences that are exteriorized through the children's interactions with these objects. Thus, the present work intends to investigate the semiotic modes and resources that stand out the most in the composition of toy-books from the child's interaction with the chosen book, with a closer look at its materiality, seeking to understand how it resignifies reading through play, or play itself, based on the reading practices provided. Specifically, we intend to describe the materiality of the toy-book in the light of the theory of “Toy Literacy” (ALMEIDA, 2020) as well as the Grammar of Visual Design (KRESS; VAN LEEUWEN 2006 [1996]); observe the child interacting with the toy-book to understand the type of relationship established between these two actors and describe other modes and places of reading and playing inserted from this category of book in the child's multiliteracy practices. In terms of theoretical basis, we have the theory of Social Semiotics and, as methodologies based on SS, we use: Literacy of Brinquedo, by Almeida (2020); as well as the tripartite framework of Serafini (2010) for the development of questions that contributed to the mediation of the researcher's contact with the child, in addition to other scholars who helped us to think about children's literary reading, the toy book, the child's development , among other themes that surround our work: Paiva (2010), Zilberman and Lajolo (1996), Cademartori (2010), Pinto and Sarmento (1997), Sirota (2001, 2011), Silveira and Afonso (2009), Vigotski ( 1996), among others. The research assumes an exploratory, descriptive and explanatory characterization, using bibliographic and field research to obtain data, with a qualitative-interpretative approach, through a logbook and photographs of children interacting with the book- toy. Our data total 15 toy-books, 5 of which were effectively used in interaction with 9 children. The analyzes and results demonstrate that one of the most relevant aspects for the promotion of multimodal reading is the materiality of these books and their possibilities of resources, establishing a relationship of ludicity sometimes provided by the practice of direct reading, be it visual, verbal, tactile, sometimes provided by the play that led to countless narratives. In addition, we found that the toy-book, based on its proposal, leads the child to occupy other spaces and ways of reading, expanding the concept of reading. Finally, the toy-book has the potential to be a representation for good quality literary texts with interesting stories that aim either not to teach a theme directly or to be just a toy.